2012
DOI: 10.1016/j.jcps.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Between a rock and a hard place: The failure of the attraction effect among unattractive alternatives

Abstract: Many important decisions that consumers face involve choosing between options that are unattractive or undesirable—the proverbial “lesser of two evils.” Consumers, who face budget or geographical constraints, for example, end up with mostly undesirable consideration sets; yet a choice is necessary. We examine the role of option set desirability in the context of the well‐established attraction effect. In five studies, we show that the attraction effect occurs in desirable domains but is eliminated when all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 51 publications
4
39
0
Order By: Relevance
“…Our results, however, also hint at the possibility of other mechanisms at play. In fact, we agree with others who have suggested that multiple mechanisms likely contribute to these context effects (Huettel et al 2009, Malkoc et al 2013.…”
Section: Limitations and Future Research Directionssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results, however, also hint at the possibility of other mechanisms at play. In fact, we agree with others who have suggested that multiple mechanisms likely contribute to these context effects (Huettel et al 2009, Malkoc et al 2013.…”
Section: Limitations and Future Research Directionssupporting
confidence: 92%
“…For personal use only, all rights reserved. Malkoc et al (2013) have found that the attraction effect is attenuated or eliminated in undesirable domains when alternatives are unattractive. Other work has shown that the amount of time elapsed, elaboration, or distraction during a decision might affect choices via other routes (e.g., , Wolf et al 2008, Dijksterhuis et al 2006, Heyman et al 2004.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Similarly, Malkoc, Hedgcock, and Hoeffler (2013) provide evidence that the attraction effect is strongly limited when the attributes are expressed as losses. For example, they show that, in general, high-price/high-quality decoys have a greater impact among respondents who desire and can afford to pay for high-quality products.…”
Section: An Undesirable Decoymentioning
confidence: 88%
“…The context in which an offer is presented therefore matters even when, by the independence of irrelevant alternatives, it should not matter for a rational decision maker. The literature on the attraction effect is vast (recent papers include Park and Kim, 2005;Malkoc et al, 2013) but the robustness of its results has recently been put into question (Frederick et al, 2014;Yang and Lynn, 2014). Most papers test the attraction effect with designs in which one compares a choice set with no dominated option and a choice set with an additional dominated option.…”
Section: Introductionmentioning
confidence: 99%